MATHEMATICAL MODELING OF THE TERMINATION FLIGHT CONTROL ALGORITHM FOR UNMANNED AERIAL VEHICLE - Kondrashov, Ya.; Arutyunyan, A.; Kravchyshyn, I. (Science-based technologies, 2010)
The efficiency of the algorithm of control synthesis is evaluated by means of mathematical modeling by a methodicalerror of the guidance of the gliding aircraft descending to the omnidirectional radio beacon. It’s shown,that the control synthesis results in formation of convergent stable process of motion parameters variation, andthe guidance error is generally determined by navigational errors of current phase coordinates determination.